2011
DOI: 10.1002/uog.8971
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computerized tomography enteroclysis vs. rectal water contrast transvaginal ultrasonography in determining the presence and extent of bowel endometriosis

Abstract: Objectives To compare the accuracy of multidetector computerized tomography enteroclysis (MDCT-e) and rectal water contrast transvaginal ultrasonography (RWC-TVS) in determining the 97.9% (47/48), 97.8% (45/46), 94.0% (47/50) and 95.8% (92/96)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 40 publications
3
63
1
1
Order By: Relevance
“…Out of theses 12 articles, two studies evaluated the diagnostic value of SCSV in detecting DPE (4,19), three studies evaluated TG-TVS (20,38,39), and another three assessed RWC-TVS (21,37,40). Surprisingly, only two articles tested the TVS with bowel preparation (13,22), and finally two articles evaluated the diagnostic value of TVS sliding sign to identify DPE (23,41).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Out of theses 12 articles, two studies evaluated the diagnostic value of SCSV in detecting DPE (4,19), three studies evaluated TG-TVS (20,38,39), and another three assessed RWC-TVS (21,37,40). Surprisingly, only two articles tested the TVS with bowel preparation (13,22), and finally two articles evaluated the diagnostic value of TVS sliding sign to identify DPE (23,41).…”
Section: Resultsmentioning
confidence: 92%
“…In the first round of literature search, out of 317 manuscripts, only 17 articles were included according to the inclusion and exclusion criteria (4,9,16,19,21,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The following rounds of literature screen to detect manuscripts regarding modified techniques of TVS identified 12 eligible manuscripts, of which three were already identified in the first literature search (4,19,21) and nine were new manuscripts (13,20,22,23,(37)(38)(39)(40)(41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biscaldi et al . proposed the use of multi‐slice computed tomography (MSCT) enteroclysis in determining the presence and depth of bowel endometriotic lesions, with excellent results compared with rectal water contrast TVS (accuracy, 97.9% and 95.8%, respectively). The most relevant disadvantage of MSCT enteroclysis is the exposure to radiation, particularly because the majority of patients are at reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…Transvaginal sonography (TVS) currently represents the first line of investigation for the diagnosis of rectosigmoid endometriosis. Previous studies have shown that TVS is as accurate as rectal endoscopic sonography, magnetic resonance imaging and multidetector computerized tomography enema for the diagnosis of rectosigmoid endometriosis. Furthermore, TVS is inexpensive compared with radiological imaging, it is well tolerated by the patient, non‐invasive and it does not require anesthesia.…”
Section: Introductionmentioning
confidence: 99%